Analisis Persepsi Mahasiswa terhadap Metode Pembelajaran Outdoor pada Mata Kuliah Taksonomi Tumbuhan - Agel Adha; Novinovrita M. (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2026)
Outdoor learning in the Plant Taxonomy course is implemented to provide direct learning experiences in nature and to overcome the limitations of classroom-based instruction. This study aims to analyze students’ perceptions of outdoor learning, identify its advantages and disadvantages, and explore the factors that influence these perceptions as well as students’ suggestions for further development. The research employs a qualitative phenomenological approach using structured interviews and thematic analysis with data reduction steps aimed at filtering relevant data from the interview results.The results show that outdoor learning enhances students’ understanding of the material, learning motivation, observational skills, teamwork, and ecological awareness. The discussion indicates that field experiences help students grasp abstract concepts more easily, although several challenges remain, such as weather conditions, limited time and facilities, and the readiness of both lecturers and students. In conclusion, outdoor learning is considered effective in supporting the Plant Taxonomy course and is recommended for broader implementation in other relevant biology courses. This study contributes by phenomenologically analyzing students’ perceptions of outdoor learning in the Plant Taxonomy course, grounded in the experiential learning theory of David A. Kolb. It identifies in a balanced manner the positive and negative aspects, as well as the factors influencing students’ perceptions, thereby providing an empirical basis for developing more contextual and participatory biology learning.